Influence of Electromagnetic Generalized Thermoelasticity Interactions with Nonlocal Effects under Temperature-Dependent Properties in a Solid Cylinder - shaaban khader; ayman marrouf; mona khedr (Mechanics of Advanced Composite Structures)
The temperature-dependent properties and the effect of non-local elasticity in the presence of a magnetic field have been studied in an infinitely long solid conductive circular cylinder. The issue arises in the setting of two relaxation times in extended magneto-thermoelasticity theory. In the presence of a uniform magnetic field in the direction of the axis, the lateral surface is traction-free and subjected to known temperatures. Techniques are employed to determine the answer in the Laplace transform domain. A numerical method based on Fourier series expansions is used to carry out the inversion operation. In addition, graphs depict comparisons to highlight the influence of various elements such as the difference in times and the effect of the non-local coefficient and Empirical material constant.